On the triviality condition for the kernel of the linearized first boundary-value problem for a system of equations of magnetic hydrodynamics - Britov, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The first boundary-value problem for a system of equations of magnetic hydrodynamics in a cylinder of infinite length with ideally conducting surface is considered under conditions in the case where it has a two-dimensional solution. Sufficient conditions are obtained for the problem linearized in the neighborhood of this solution to have the trivial solution.